Application of Interactive Multi-Biometrics Recognition on E-Commerce - Ling Tan; Lu Zhang (Dianxin kexue)
An interactive multi-biometrics recognition method was proposed，and its application on e-commerce was researched from third-party payment platform.For our interactive multi-biometrics recognition，the identification of users was accomplished with the recognition of multi-biometrics features like nose，ear，and finger-knuckle-print.Payment confirmation and signature were achieved with interactive face scan and fingerprint identification.A frame of third party payment platform was designed，based on which a simple and light-weighted pre-authentication layered model for online payment was established.This model can well guarantee security and reliability of payers，sellers，and banks，simplify the process of payment for users as well.